A co-creativity theoretical framework to foster and evaluate the presence of wise humanising creativity in virtual learning environments (VLEs). (June 2017) - Walsh, Chris; Chappell, Kerry; Craft, Anna
Highlights: A co-creativity theoretical framework to evaluate wise humanising creativity (WHC) is proposed. A co-creativity assessment methodology to evaluating the presence of WHC is presented. A new theoretical framework to foster and evaluate WHC in virtual learning environments (VLEs). Abstract: Wise humanising creativity (WHC) is creativity guided by ethical action, meaning it is mindful of its consequences and is empowering, offering far greater shared hope for the future than the competitive mentality that pervades most education systems. Understanding how virtual learning environments (VLEs) can foster WHC is becoming exceedingly important because it problematizes the marketisation of childhood and youth. It also offers new ways of considering educational futures including implications for the theoretical understanding of creativity within VLEs. We report on the theoretical development of the concept of WHC within C 2 Learn, a three-year project designing a digital gaming environment that provides children and young people with multiple opportunities to engage in co-creativity to foster their WHC. C 2 Learn is the first time WHC has actively been conceptualised in a digital context. We present our over-arching co-creativity conceptual framework which has been developed to frame the specific kind of co-creativity that is envisaged within C 2 Learn's VLE. Drawing on that framework, we present a co-creativity assessment methodology specifically focused on evaluating the presence of WHC. We argue that leveraging WHC within VLEs broadens perspectives on the purposes of education, as this ethically framed creativity foregrounds the role of values in generating fundamental small-scale creative change through 'journeys of becoming' that have the potential to generate 'quiet revolutions' or small cumulative, incremental changes over time which are meaningful to a particular community.